VIRTUAL REALITY SYSTEM FOR JOB INTERVIEW APPLICATION: A DEVELOPMENT RESEARCH - Jailani, Moh. Kholilurrahman; Nurbatra, Laela Hikmah (Celtic: A Journal of Culture, English Language Teaching, Literature and Linguistics, 2019)
Technology has become more sophisticated and widely used in pedagogical process. One of sophisticated technologies that is recently known and became attractive towards the public attention is Virtual Reality. This system applied simulated object and artificial environment like the real-world version. A need analysis conducted by Jailani (2017)on the use of VR for Business English students indicated that the students were interested and enthusiastic to learn job interview.The objective in the current research is to develop Virtual Reality System for Job Interview in Business English class at University of Muhammadiyah Malang. In doing so, the present research applied seven procedures in Research and Development design which aimed to develop some features and contents that are applied on Job Interview application. The subjects of this research are students from Business English (BE) class, English Language Education Department of UMM academic year 2016/2017. Observation, questionnaire, and documentation were employed to collect the data. The data were then transcribed and analyzed to reach the research purpose.The result revealed that the application is in very valid category that reached 93.33% for product and design validation; while 93.75% for content validation. Moreover, additional features were developed on stuffs, scoring system, and button to make the users more interested in using VR. In addition, it was found that the students of Business English as users were motivated and attracted in conducting job interview simulation through Virtual Reality